Efektivitas Pembelajaran Kontekstual dalam Meningkatkan Kemampuan Siswa Menyelesaikan Soal Matematika Berbasis HOTS (Higher Order Thinking Skill) - Moh Supratman (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine the effectiveness of contextual learning in improving students' ability to solve math problems based on HOTs (Higher Order Tinking Skill). This type of research is experimental research, the research design uses a one group pretest-posttest design. The research subjects were students of class VIIA SMP Negeri 2 Praya Timur, totaling 42 students. The data collection instrument used a written test in the form of an essay (essay), and data analysis used the t test. Based on the results of descriptive statistical analysis, it shows that the pretest results of students in solving HOTs-based questions are still low with an average of 31.07, and after being given treatment by applying a contextual learning approach, students' ability to solve HOTs-based questions based on the posttest average increased to 84 .57 with very high category. While the results of the t-test with a test-value of 65 obtained tcount = 15.515, for a significance value of 0.000. In conclusion, the contextual learning approach is effective in improving students' ability to solve HOTs-based questions. Keywords: Contextual Learning, HOTS-Based Questions